The role of the spiritual dimension in medical decisions - Petralia, Paolo; Ciliberti, Rosagemma (Medicina Historica, 2023)
Spirituality and science, in medicine, belong to worlds that are only apparently distant and irreconcilable.Clinical practice constantly testifies how they, while maintaining their own identity, walk in parallel, influencing and supporting each other in defining a treatment path.The anthropological perspective of the concept of health also refers to recognizing the breadth and complexity of its dimension, as the result of an intricate set of biological, psychic, social, cultural and spiritual factors, in a continuous relationship with the environment in which the individual lives and interacts. This awareness calls for a peculiar consideration and attention towards this dimension, which also requires an adequate preparation of health personnel and clinicians to recognize and take charge of the spiritual needs of the patients.The cultural process that goes by the name of "humanization of care" constitutes the terrain that must be explored in order to attempt the reconciliation between science and spirituality.